Determinants of capital formation in the Malaysian rubber estate sector - Habibullah, Muzafar Shah (FAO, 1989)
This study empirically determines the factors affecting capital formation in the Malaysian rubber estate sector. A partial adjustment adaptive expectation model was tested on annual time series data over the period 1961 to 1985, + The results suggest that capital formation in Malaysian rubber estates is determined by future prices of rubber, interest rate on financial assets, interest rate on agricultural loans and size of holdings. The results indicate at least two areas where + the government can play an active role in promoting investments in the rubber estate sector, i.e. by providing cheap funds by varying the interest rate on loans in favour of producers, and sustaining income by stabilising rubber prices.